2012
DOI: 10.1126/scitranslmed.3003726
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Identification and Monitoring of Cancer Mutations by Targeted Deep Sequencing of Plasma DNA

Abstract: Plasma of cancer patients contains cell-free tumor DNA that carries information on tumor mutations and tumor burden. Individual mutations have been probed using allele-specific assays, but sequencing of entire genes to detect cancer mutations in circulating DNA has not been demonstrated. We developed a method for tagged-amplicon deep sequencing (TAm-Seq) and screened 5995 genomic bases for low-frequency mutations. Using this method, we identified cancer mutations present in circulating DNA at allele frequencie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
964
3
8

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,131 publications
(990 citation statements)
references
References 42 publications
(85 reference statements)
15
964
3
8
Order By: Relevance
“…6,18e21 However, to date there have been no rigorous studies comparing sequence data obtained from routine clinical FFPE tissue to paired fresh frozen tissue. A recent study by Forshew et al 18 found a similar background frequency of nonreference base changes in 47 FFPE samples enriched by multiplex PCR. In another study, Kerick et al 21 reported a false-positive rate of 0.98% for SNV calls from low coverage (Â20) NGS data from FFPE tissue; the authors note, however, that the false-positive rate can be reduced with increased (> Â80) coverage.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…6,18e21 However, to date there have been no rigorous studies comparing sequence data obtained from routine clinical FFPE tissue to paired fresh frozen tissue. A recent study by Forshew et al 18 found a similar background frequency of nonreference base changes in 47 FFPE samples enriched by multiplex PCR. In another study, Kerick et al 21 reported a false-positive rate of 0.98% for SNV calls from low coverage (Â20) NGS data from FFPE tissue; the authors note, however, that the false-positive rate can be reduced with increased (> Â80) coverage.…”
Section: Discussionmentioning
confidence: 73%
“…18 We therefore conducted additional analysis to determine whether fixation-induced DNA artifacts could be detected at low levels. To enrich for true base changes in the parent library molecules and avoid sequencing errors, only discrepancies in high-quality read alignments with a minimum mapping quality score of 20 were considered, and discrepant bases were required to have base qualities of at least 20; positions called as SNVs by a standard variant identification method were also excluded.…”
Section: Evaluation Of Formalin Fixationeinduced Sequencing Artifactsmentioning
confidence: 99%
“…Researchers soon found similar results for other types of cancer. Rosenfeld and his Cancer Research UK colleagues James Brenton and Carlos Caldas showed that ctDNA provides a precise portrait of advanced ovarian and breast cancers 8 . And in the largest study yet, Diaz and other members of the Johns Hopkins group detected ctDNA in at least 75% of patients with advanced tumours, in organs as diverse as the pancreas, bladder, skin, stomach, oesophagus, liver and head and neck 9 .…”
Section: By E D Yo N Gmentioning
confidence: 99%
“…The advances we present have practical implications for inference of clonal populations, and show measurable reductions in spurious inference relative to current approaches. As the practice of measuring allelic prevalences during the treatment cycle 15,16 or through retrospective analysis of multiple samplings increases 10, 14, 17 , we suggest PyClone will contribute a robust statistical inference approach for studying selection patterns underpinning disease progression in cancer.…”
mentioning
confidence: 99%